Influencia de los programas de aprendizaje socioemocional (SEL) en el desempeño académico escolar de niños y adolescentes - Forga Garland, Ximena (2022)
Social and emotional development can be a factor that sustains a relationship with school academic performance. This review aims to know the influence of Social and Emotional Learning (SEL) programs on school academic performance. Research has been included that includes indicators of academic performance according to the subjects of the school, in a specific academic sense, as well as social and emotional indicators, to identify these same variables and school performance from a broader perspective according to the SEL model. To achieve the objective, an applied review was carried out, following the PRISMA (Urrútia and Bonfill, 2013) guide, identifying the eligibility criteria, search strategy and selected databases. The participating population ranges from pre-school age to the end of primary, as this allows an analysis of the results at different school stages. The results allowed to recognize, through 10 longitudinal and/or experimental quantitative investigations, SEL programs influence academic performance. Finally, discussions between the findings, limitations and suggestions are presented, including the perspective regarding the current Peruvian circumstances.